2023
DOI: 10.1186/s12938-023-01093-z
|View full text |Cite
|
Sign up to set email alerts
|

3D shape reconstruction of the femur from planar X-ray images using statistical shape and appearance models

Abstract: Major trauma is a condition that can result in severe bone damage. Customised orthopaedic reconstruction allows for limb salvage surgery and helps to restore joint alignment. For the best possible outcome three dimensional (3D) medical imaging is necessary, but its availability and access, especially in developing countries, can be challenging. In this study, 3D bone shapes of the femur reconstructed from planar radiographs representing bone defects were evaluated for use in orthopaedic surgery. Statistical sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…This method can be utilized in deformable 2D-3D registration by considering the dynamic and flexible nature of anatomical structures, which is a crucial advancement along with existing techniques. [37][38][39] Thus, the use of a particle-based SSIM and its projection methods represents a significant step forward in deformable registration medical imaging, offering improved adaptability in patient-specific bone modeling and kinematics assessments.…”
Section: Discussionmentioning
confidence: 99%
“…This method can be utilized in deformable 2D-3D registration by considering the dynamic and flexible nature of anatomical structures, which is a crucial advancement along with existing techniques. [37][38][39] Thus, the use of a particle-based SSIM and its projection methods represents a significant step forward in deformable registration medical imaging, offering improved adaptability in patient-specific bone modeling and kinematics assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, when it comes to fractures, the bone data acquired from medical imaging techniques can often be incomplete, lacking the necessary geometric and anatomical information required to construct a complete bone model. Various approaches and methodologies can be employed to develop a 3D model of the bone, utilizing either complete data (standard reverse modeling) or incomplete data (template and/or parametric models) [6,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of MAF has been demonstrated through various studies [6,7,19], which have shown its geometrical accuracy as well as its anatomical and morphological correctness when applied to human bones. Further examples of MAF application can be found in chapters [10][11][12] of the book "Personalized Orthopedics" [31] published by Springer. In addition to bones, MAF has been utilized in the creation of personalized implants for human bones, including long and flat bones.…”
mentioning
confidence: 99%